The Impact of Mechanization Under UPJA Program on Rice Farming Income in Prambanan Sub-District Sleman District - Kurnia Arif Oktovianto; Irham Irham; Suhatmini Hardyastuti (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2018)
The Agricultural machinery rental services (UPJA) program has an important role on the application of agricultural mechanization and increasing farming income. This study aims: (1) to compare the farm costs between the farmers who apply mechanization under UPJA program and those who do not (Non-UPJA), and (2) to know the effect of implementing agricultural mechanization and the other factors toward farm income in Prambanan Sub-District, Sleman District. The data collected consists of 25 farmers who apply agricultural mechanization under UPJA program, choosen by sensus and 25 farmers who do not apply (Non-UPJA), choosen by using proporsional random sampling. To determine the differences of farm costs, farming analysis and mean difference test using independent sample t-test was applied. To determine the effect of mechanization toward farm income, multiple liniear regression analysis was used. The result of mean difference test showed that there is no significant differences of farm costs between UPJA and Non-UPJA farmers. The result of multiple liniear regression analysis showed that mechanization has significant effect to the farm income. Farm income of the farmers who apply mechanization under UPJA program is significantly higher than the farmers who do not. Other factors that have significant effect to farm income are land area, price of organic fertilizer and price of ZA fertilizer.